Prevention is Better than Prosecution: Deepening the Defence against Cyber Crime - Fick, Jacqueline (Journal of Digital Forensics, Security and Law, 2009)
In the paper the author proposes that effectively and efficiently addressing cyber crime requires a shift in paradigm. For businesses and government departments alike the focus should be on prevention, rather than the prosecution of cyber criminals. The Defence in Depth strategy poses a practical solution for achieving Information Assurance in today’s highly networked environments. In a world where “absolute security” is an unachievable goal, the concept of Information Assurance poses significant benefits to securing one of an organization’s most valuable assets: Information. It will be argued that the approach of achieving Information Assurance within an organisation, coupled with the implementation of a Defence in Depth strategy can ensure that information is kept secure and readily available and provides a competitive advantage to those willing to invest and maintain such a strategy